Obesity and age as dominant correlates of low testosterone in men irrespective of diabetes status. (30th September 2013) - Ng Tang Fui, M.; Hoermann, R.; Cheung, A. S.; Gianatti, E. J.; Zajac, J. D.; Grossmann, M.
Summary: Although men with type 2 diabetes (T2D) frequently have lowered testosterone levels, it is not well established whether this is ascribable to the diabetic state per se, or because of other factors, such as obesity. Our objective was to determine the prevalence and correlates of low testosterone in middle‐aged men with diabetes. We conducted a cross‐sectional study in 240 men including 80 men with type 1 diabetes (T1D), 80 men with T2D and 80 men without diabetes. Prevalence of a total testosterone ≤8 nmol/L was low, occurring in none of the men with T1D, 6.2% of men with T2D and 2.5% of men without diabetes. Men with T1D had higher testosterone levels compared with men without diabetes ( p < 0.001), even after adjustment for body mass index (BMI) and age ( p < 0.02). While men with T2D had lower testosterone compared with controls ( p = 0.03), this was no longer significant when BMI and age were taken into account ( p = 0.16). In the entire cohort, TT remained inversely associated with BMI independent of age, sex hormone‐binding globulin and diabetic status ( p = 0.01), whereas calculated free testosterone (cFT) was independently and inversely associated with age ( p < 0.001), but not with BMI ( p = 0.47). These results suggest that marked reductions in circulating testosterone are uncommon in middle‐aged men with diabetes. Increasing BMI and age are dominant drivers of lowered total and cFT, respectively, independent of the presence or absence of diabetes.